Transmissibility of asymptomatic COVID-19: Data from Japanese clusters - Nakajo, Ko; Nishiura, Hiroshi (International journal of infectious diseases, 2021)
•Cluster-based approach in Japan brought all contacts under close observation with laboratory testing.•The very first cluster in Tokyo and Kanagawa (n = 36) that included 12 asymptomatic individuals was analyzed.•Relative infectiousness of asymptomatically infected cases was estimated to be 0.27 (95% CI: 0.03–0.81) of symptomatic cases. The epidemiological importance of asymptomatic individuals who would never develop illness, compared to those who eventually develop symptoms, has yet to be fully clarified. The very first cluster data in Tokyo and Kanagawa (n = 36) were analyzed. Movement of all close contact was restricted for 14 days and they underwent laboratory testing with polymerase chain reaction. The reproduction numbers of symptomatic and asymptomatic cases were estimated. The reproduction number for symptomatic cases was estimated to be 1.2 (95% confidence interval (CI): 0.5–2.9). The relative infectiousness of asymptomatically infected cases was estimated to be 0.27 (95% CI: 0.03–0.81) of symptomatic cases. The relative transmissibility of asymptomatic cases is limited. Observing clusters starting with symptomatic transmission might be sufficient for the control.